Pyrite-Type CoS2 Nanoparticles Supported on Nitrogen-Doped Graphene for Enhanced Water Splitting - Zhang, Wei; Ma, Xiaoya; Zhong, Cheng; Ma, Tianyi; Deng, Yida; Hu, Wenbin; Han, Xiaopeng (Frontiers in Chemistry, 2018)
It is extremely meaningful that developing cheap, highly efficient and stable bifunctional electrocatalysts for both hydrogen and oxygen evolution reactions (HER and OER) to promote large-scale application of water splitting technology. Herein, we reported the preparation of CoS2 nanoparticles supported on nitrogen-doped graphene (CoS2@N-GN) by one-step hydrothermal method and the enhanced electrochemical efficacy for catalyzing hydrogen and oxygen in water electrolysis. The CoS2@N-GN composites are composed of interconnected nitrogen-doped graphene and CoS2 nanocrystals with sizes in the range of 60-70 nm. Benefitting from the synergistic effect, the as-prepared CoS2@N-GN exhibits remarkable OER and HER performance in 1.0 M KOH, with overpotentials of 243 mV for the OER and 204 mV for the HER at 10 mA cm−2, and the corresponding Tafel slopes of 51.8 and 108 mV dec−1, respectively. Otherwise, the CoS2@N-GN hybrid exhibits superior long-term catalytic durability. Moreover, an alkaline water splitting device assembled by CoS2@N-GN as both anode and cathode can achieve a low cell voltage of 1.53 V at 60 °C with a good high faraday efficiency of 100% for overall water splitting. The tremendously enhanced electrochemical behaviors arise from favorable factors including small sized, homogenously dispersed novel CoS2 nanocrystals and coupling interaction with the underlying nitrogen-doped graphene, which would provide insight into the rational design of transition metal chalcogenides for highly efficient hydrogen and oxygen-involved electrocatalysis.